2009
DOI: 10.1098/rspb.2009.1146
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive basis of geographic variation: genetic, phenotypic and environmental differences among beach mouse populations

Abstract: A major goal in evolutionary biology is to understand how and why populations differentiate, both genetically and phenotypically, as they invade a novel habitat. A classical example of adaptation is the pale colour of beach mice, relative to their dark mainland ancestors, which colonized the isolated sandy dunes and barrier islands on Florida's Gulf Coast. However, much less is known about differentiation among the Gulf Coast beach mice, which comprise five subspecies linearly arrayed on Florida's shoreline. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 52 publications
7
60
0
Order By: Relevance
“…This might suggest a functional effect of the MC1R haplotype on pheomelanin, in particular of the non-synonymous variant c.502A>G. However, only molecular biology experiments could prove that this variant is indeed the functional mutation that influences the pelage color. A similar example of MC1R effect was previously shown in a study of subspecies of the Gulf Coast beach mice where a strong association was found between MC1R genotypes, pigmentation and background sand brightness, consistent with local adaptation [43]. In pocket mice, four of nine MC1R non-synonymous variants were observed in the dark mice from the Pinacate locality.…”
Section: Discussionsupporting
confidence: 81%
“…This might suggest a functional effect of the MC1R haplotype on pheomelanin, in particular of the non-synonymous variant c.502A>G. However, only molecular biology experiments could prove that this variant is indeed the functional mutation that influences the pelage color. A similar example of MC1R effect was previously shown in a study of subspecies of the Gulf Coast beach mice where a strong association was found between MC1R genotypes, pigmentation and background sand brightness, consistent with local adaptation [43]. In pocket mice, four of nine MC1R non-synonymous variants were observed in the dark mice from the Pinacate locality.…”
Section: Discussionsupporting
confidence: 81%
“…The shifts in relative morph frequencies seen between individuals in founding groups and established populations are indicative of selection, but may also reflect differences among morphs in degree of parent-offspring resemblance. We consider selection for camouflage mediated by differential predation [19,23,31,32] to be one of the most important mechanisms behind the observed pattern. Their small size and locally high population densities render grasshoppers susceptible to visual predators such as birds [31,33] and lizards [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it demonstrates the full realization of the modern synthesis: Darwinian concepts of selection have been rendered quantitative and measurable in real populations, thanks to methodological and technological advances (1). Through evolutionary genetics, many different traits became uncovered, from lactase persistence and skin pigmentation in humans (89,123), to coat color in field mice (80), to armored plates in stickleback fish (63). With ongoing advancements in genomic technology, we can now go further, from testing evidence for selection on specific traits hypothesized to be adaptive, to uncovering candidate regions through genome scans.…”
Section: Introductionmentioning
confidence: 95%